A BOUNDARY ELEMENT METHOD FOR STEADY INFILTRATION FROM A SINGLE CHANNEL - N. WIDANA; MARIA LOBO (Jurnal Matematika, 2007)
The matric flux potential and horizontal and vertical flux distributions are obtained usingintegral equation techniques for a single irrigation channel. The theory is based on the assumptionthat the hydraulic conductivity is an exponential function of the soil water potential. In therelevant special cases the results are compared with results obtained previously by Batu [4] andWarrick and Loman [20].